Søren Rinder Bollerup og Christian Dons Christensen, Nationalism in Eastern Europe. Causes and Consequences of the National Revivals and Conflicts in Late Twenthieth-Century Eastern Europe: London: Macmillan; New York: St. Martin's Press, 1997, 308 s. - Skak, Mette (Politica, 1998)
-